IMPLEMENTASI APLIKASI E-COMMERCE BERBASIS WEB - Penny Hendriyati; Afrasim Yusta (JURSIMA, 2021)
Web-based e-commerce applications make it easy for online shop businesses to promote their products and make it easier for customers to get information about the seller’s products. The role of online information systems is currently being used as a means of increasing information. Nayadicka OlShop is a home based business that sells boutiques, the owner of which is Nayadicka. So far, the limitations of product marketing have become an obstacle for sellers in increasing sales turnover of sales processing systems that are less than optimal, and the difficulty of reaching customers and making reports that are still manual is a bad impact on shop owners so that product sales data reports are blocked. The purpose of this research is to improve the service quality of Nayadicka OlShop, solve sales problems, provide effectiveness and efficiency in labor and time, increase sales reach in a wider scope and simplify the process of presenting data. The method used for this research is the waterfall method. System design uses Context Diagrams, Data Flow Diagram (DFD), PHP Programming language and MySQL database. This research produces a web-based e-commerce applications that provides real-time information, product data sales reports, promotes products sold more widely so that can increase sales and can be used by customers and admin Nayadicka OlShop anytime and anywhere efficiently and effectively. Keywords : Systems Design, E-Commerce, Waterfall, Web